دراسة مقارنة لبعض المتغيرات البايوكينماتيكية بين مرحلتي تزايد السرعة وتحمل السرعة في ركض 100 متر للعداءات - علو, ثائر غانم ملا; عثمان, فريدون حسن (Sulaimani Journal for Humanities, 2018)
The 100m event is one of the track and field events that deal with the maximum effort of the racer with the accuracy of performance from the first moment to start to the finish line. The speed of the 100 m passes through multiple stages, and this stage is the stage of increasing the speed (acceleration phase), in which the speed increases by different length of the step and frequency and there is another stage of speed bearing and the speed decreases through the difference length of the step and frequency So the problem of our search to be similar to the difference between some variables Kinematic length of the running stage is increasing speed and the endurance stage of speed for the runners. The aim of the research is to identify the values of some biokenmatic variables for the stages of increasing and the endurance speed in running 100 m for the racers and to identify the differences in the values of some biokenmatic variables between the two stages. The researchers used the descriptive style survey. The research sample was selected purposively in a manner representing the runners (100 m) to the province of Erbil. Totaling (5) runners. The motion analysis was performed using computer to reach the values of kinematics’ variables. And the use of the statistical program (SPSS) to Data processing and the researchers found that there is a difference in the distance between the distance step of increasing speed and endurance speed. And a difference in the time of the step between the stage of increasing speed and endurance speed.